IMPLEMENTASI KEBIJAKAN SISTEM JAMINAN KESEHATAN IBU HAMIL DALAM RANGKA MEMPERCEPAT PENCAPAIAN MILLENIUM DEVELOPMENT GOALS - MDG′S DI KOTA BANJARMASIN, KALIMANTAN SELATAN - Suroyo, Anis (JPAP: Jurnal Penelitian Administrasi Publik, 2016)
Maternal and child health is one of the Millennium Development Goals MDG's 2015global agreement targeting the maternal mortality rate in Indonesia can be reduced to 102per 100,000 live births in 2015. Efforts to suppress AKI continue to be pursued, includingthe provision of health services for pregnant women. In 2014, the government beganimplementing a National Health Insurance (JKN) nationally. Implementation of the JKNprogram causes Delivery Guarantee (Jampersal) for pregnant women deleted. The deletionencourage local governments to be creative pressing AKI with JKN program and theRegional Health Insurance (Jamkesda). Policy of Implementation Security SystemMaternal Health in Banjarmasin, which inhibits MCH program because the program JKNknows no territorial, pregnant women can choose the health care she likes, while the MCHprogram is monitoring the health of pregnant women by the cantonal ie PWS-KIA forevaluation and program planning region. The cause of the mortality rate among pregnantwomen in the city of Banjarmasin is due late in delivery to the referral occurs as a result offactors helper (service providers at a basic level), delayed detection of high risk so that thecondition of pregnant women who were referred is severe enough, and too late to reachhealth care at the level of referral services. Lack of adequate resources, facilities andinfrastructure that do not support and quality of service at referral level is a factor causingdelay in rescue efforts maternal health. JKN program bureaucratic system does not supportMCH programs, thus largely independent midwives are reluctant to deal with pregnantwomen / mothers give birth this was due to a convoluted bureaucracy and services /approved rates are too low in accordance with Law of the Ministry of health No 59, 2014. Key words: implementation of policies, health insurance pregnant women